2007
DOI: 10.1021/la701972n
|View full text |Cite
|
Sign up to set email alerts
|

A Carbonate Controlled-Addition Method for Amorphous Calcium Carbonate Spheres Stabilized by Poly(acrylic acid)s

Abstract: Stable amorphous calcium carbonate (ACC) composite particle with a size-controlled monodispersed sphere was obtained by a new simple carbonate controlled-addition method by using poly(acrylic acid) (PAA) (Mw = 5000), in which an aqueous ammonium carbonate solution was added into an aqueous solution of PAA and CaCl2 with a different time period. The obtained ACC composite products consist of about 50 wt % of ACC, 30 wt % of PAA, and H2O. Average particle sizes of the ACC spheres increased from (1.8 +/- 0.4) x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
127
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 63 publications
5
127
0
3
Order By: Relevance
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
See 3 more Smart Citations
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
“…This rapid process makes it difficult to study the properties of ACC and the mechanism of the mineralization process. Some specific additives, such as organic macromolecules and magnesium ions, have been used to stabilize ACC nanospheres by forming complexes with metal ions [44,46,47]. Huang et al [47] reported a poly(acrylic acid) (PAA)-assisted method to synthesize highly stable, size-controlled monodisperse ACC nanospheres.…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
See 2 more Smart Citations
“…(6) Several techniques have been reported for the synthesis and stabilization of ACC, (4,7) but all known methods use either toxic materials or various organic polymers to stabilize ACC for more than 3 days. (7)(8)(9)(10)(11) To avoid use of such compounds, a novel method for synthetic production of stabilized ACC using phosphoaminoacids was developed recently (12) and was shown to stabilize ACC for more than 4 months under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%